1992
DOI: 10.1002/jbm.820261103
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ultrastructures of the interfaces between four kinds of surface‐active ceramic and bone

Abstract: The interfaces between four kinds of surface-active ceramic and bone were studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) using undecalcified specimens. The materials were Bioglass-type glass (Bioglass), Ceravital-type glass-ceramic (KGS), apatite- and wollastonite-containing glass-ceramic (A-W.GC) and hydroxyapatite (HA). Particles of these materials, ranging between about 100 and 300 microns in diameter, were implanted into rat tibiae, and specimens were prepared for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 240 publications
(81 citation statements)
references
References 18 publications
4
76
0
1
Order By: Relevance
“…Simple chemical treatment of titanium substrate with 30 vol % H 2 O 2 solution containing 5 mol·m ¹3 tantalum chloride (TaCl 5 ) also improved apatite formation ability in SBF. 16) An enhanced bonding property was observed in vivo for titanium substrate treated by H 2 O 2 solution containing TaCl 5 . 17) Apatite formation was induced by formation of a suitable titania hydrogel layer after the treatment.…”
Section: Providing Bone-bonding Properties To Metallic Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…Simple chemical treatment of titanium substrate with 30 vol % H 2 O 2 solution containing 5 mol·m ¹3 tantalum chloride (TaCl 5 ) also improved apatite formation ability in SBF. 16) An enhanced bonding property was observed in vivo for titanium substrate treated by H 2 O 2 solution containing TaCl 5 . 17) Apatite formation was induced by formation of a suitable titania hydrogel layer after the treatment.…”
Section: Providing Bone-bonding Properties To Metallic Materialsmentioning
confidence: 97%
“…Guidelines for controlling the crystalline phases and morphology of calcium phosphates under various conditions using pH, calcium ion concentration, and phosphate ion concentration were reported. The resulting calcium phosphate crystalline phases varied from HAp to DCPD or dicalcium phosphate anhydrous (DCPA, CaHPO 4 Figure 7 shows OCP formed in silica hydrogel under various pH and temperature conditions. The morphology of OCP changed from spherical to rod-or ribbon-like with increasing reaction temperature and decreasing pH, while the morphology of HAp changed from irregular to rod-like with increasing reaction temperature and decreasing pH.…”
Section: )mentioning
confidence: 99%
“…Bioglass Ò and -TCP have been well-known as biodegradable materials with high solubility. [7][8][9][10][11] Bioglass Ò , however, has a tendency to worry about its fragility and its toxicity, originating from high silicon-releasability. It is difficult to control the biodegradability of -TCP effectively.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Bone-like hydroxyapatite b-HA layer intervenes between new bone and implanted surface-active ceramics such as HA, Cerabone A-Wଆand Bioglassଆ . 4,5 It was reported that HA bonded to bone directly or via a comparatively thin b-HA layer, and the b-HA layer with about 0.5 mm in thickness intervened between bone and Cerabone AWଆor Bioglassଆ . 5 On the other hand, new bone is directly formed on the surfaces of resorbable ceramics such as b-TCP after implantation in bone.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It was reported that HA bonded to bone directly or via a comparatively thin b-HA layer, and the b-HA layer with about 0.5 mm in thickness intervened between bone and Cerabone AWଆor Bioglassଆ . 5 On the other hand, new bone is directly formed on the surfaces of resorbable ceramics such as b-TCP after implantation in bone. These various reactions in the new bone formation depending on implanted ceramics were suspected to originate from differences in the chemical composition, crystallinity and resorbability of the ceramics in body.…”
Section: Introductionmentioning
confidence: 99%